Supply Chain Complexity Drivers and Solution Methods - Piya, Sujan; Shamsuzzoha, Ahm; Khadem, Mohammad; Al-kindi, Mahmoud (International Journal of Supply Chain Management, 2017)
Increased globalization, shorter product life cycle and rapid technological advancement in the manufacturing as well as service companies necessitates the company to have multiple supply chain partners. The partnership may be physical or virtual, thus making the chain more challenging and complex to manage. Therefore, the present supply chain network is characterized by its complexity, which requires proper management and strategy for its mitigation. In addition, the dynamic world in this complex supply chain system demands the manager to make faster and efficient decision. To manage the overall supply chain complexity and to make an efficient decision it is important that the manager understand the associated complex interactions within a supply chain, as well as, proper solution method or strategy to mitigate them. In this paper, a generic supply chain complexity drivers are identified and proposed solutions methods to manage the complexity in supply chain.